Pan-Islamism in Algeria : a study of the concept of Muslim unity in the thoughts of Hamdan Khuja and Amir Abdul Qadir - Mohadi, Mawloud (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2021)
The current study examines the ideas of Pan-Islamism in Algeria through the thoughts and activities of Hamdan Khuja and Amir Abdul Qadir, its objectives, and impediments during the colonial era. This research also attempts to evaluate Algerian nationalism and the accuracy of Hans Kohn’s “universal Theory of Social Change” on the issue of Islamic identity in Algeria in the light of the thoughts Hamdan Khuja and Amir Abdul Qadir during the first half of the nineteenth century. The researcher implemented the method of induction and textual analysis to examine the ideas of Pan-Islamism in Hamdan Khuja and Amir Abdul Qadir’s writings. This assessment of primary as well as secondary sources offers a reliable account to revisiting the concepts of Muslim unity, identity, and nationalism in Algeria. Throughout the colonial era that started in the 1830s, the French authorities described the Pan-Islamic endeavours in Algeria that aimed at Muslim reforms intellectually, religiously, socially, educationally, and politically as an anti-governmental and anti-French movement. However, this study reveals that Muslim unity in the thoughts of Hamdan Khuja and Amir Abdul Qadir was devised to emphasise on constructive reforms, solidarity and camaraderie among the entire Muslim territories. Additionally, the study proposes that the call for Muslim unity in the first half of the nineteenth century in Algeria must be studied in accordance with the tenets of Islamic thought and the perpetual ideals of Islam such as brotherhood, integrity, justice, and human rights. Islamic unity relative to the ideas of Hamdan Khuja and Amir Abdul Qadir was an endeavour of Algerian Muslims to unite spiritually and politically to consolidate their positions economically, socially, culturally, educationally, and legally against the menace from French Imperialism. Furthermore, this study shows that Algerian Pan-Islamism was never identical or equal to nationalism neither was it a primitive phase for its emergence. Throughout their anti-colonial resistance, Hamdan Kuūja, as well as Amir ‘Abdul Qadir, identified themselves as Muslims first, with no mention of any racial or tribal loyalties. Therefore, they asserted their Islamic identity and their grip to the religion. In the years that followed, the Algerian people displayed a stronghold in Islam despite the rise of national consciousness at the beginning of the twentieth century. Moreover, this study suggests that Islamic unity is entrenched within the Islamic tradition of the ummah, and it was not a new occurrence. Thus, Islam never lost its significance in colonial Algeria which refutes H. Kohn’s Theory of Social Progress. According to the thoughts of Hamdan Khuja and Amir Abdul Qadir, the study shows that Islamic unity in Algeria did not have an anti-Christian spirit but rather an anti-colonial character aiming to liberate Muslims from colonial presence. Lastly, the thoughts of Hamdan Khuja, as well as Amir ‘Abdul Qadir, offer positive perceptions on the prospects of Islamic unity and the way to achieve it. Therefore, this study accentuates the necessity for alternative approaches to studying Islamic unity and other occurrences in Muslim countries.